Helminth fauna of rodents (Mammalia, Rodentia) from Zasavica (Serbia) - Bjelić-Čabrilo, Olivera; Čabrilo, Borislav; Popović, Ester (Biologia Serbica, 2014)
Forty-four individuals of small rodents from the Zasavica locality were examined for the presence of helminth parasites. These included 12 striped field mice (Apodemus agrarius), 18 wood mice (A. sylvaticus), 2 yellownecked mice (A. flavicollis), 6 house mice (Mus musculus) and 6 voles identified only as belonging to the genus Microtus. Nine different helminth species were identified, with 8 individual roundworms identified only as genus Syphacia, and 19 individual flukes identified only as genus Brachylaima. Five species of helminth were roundworms (Capillaria murissylvatici, Heterakis spumosa, Heligmosomum costellatum, Rictularia proni, Trichocephalus muris), three were tapeworms (Hymenolepis fraterna, Rodentolepis straminea, Skrjabinotaenia lobata) and one was the fluke Plagiorchis elegans. The total prevalence of helminth infection was approximately 45%, and the dominant roundworm species was H. spumosa, which was found in around 34% of the individuals. The wood mouse was identified as a new host for the roundworms C. murissylvatici, Heterakis spumosa, Heligmosomum costellatum and R. proni, and for the tapeworms R. straminea, S. lobata and Hymenolepis fraterna on the territory of Serbia. The flukes P. elegans and Brachylaima sp. and the tapeworm S. lobata are reported for the first time on the territory of Serbia.